Health-related quality of life in breast cancer patients in low-and-middle-income countries in Asia: a systematic review - Ngo, Nhi T. N.; Nguyen, Ha Thi; Nguyen, Phuong Thi Lan; Vo, Truc Thuy Thanh; Phung, Toi Lam; Pham, Anh Gia; Vo, Thanh Van; Dang, Mai Thi Ngoc; Nguyen Le Bao, Tien; Duong, Khanh N. C. (Frontiers in Global Women's Health, 2023)
Introduction Breast cancer remains one of the major cancers worldwide. In Asia, breast cancer is leading both incidence and mortality rates. Health-related quality of life (HRQoL) studies play an important role in clinical treatment. This systematic review aimed to summarize the evidence of HRQoL and associated factors among patients with breast cancer in low-and-middle-income countries (LMICs) in Asia. Method Performed according to PRISMA guidelines for systematic review, the studies were searched from three databases (PubMed, Cochrane, Scopus) up to November 2020. The studies which met the predefined eligibility criteria were selected, extracted, and assessed the quality according to the Newcastle—Ottawa Scale (NOS) tool. Results and Discussion A total of 2,620 studies were searched on the three databases, of which 28 met the selection criteria, then, were included in the systematic review. The Global Health Status (GHS) score of breast cancer patients based on the EORTC QLQ-C30 questionnaire ranged from 56.32 ± 25.42 to 72.48 ± 15.68. The overall HRQoL scores using the FACT-G and FACT-B instruments ranged from 60.78 ± 13.27 to 82.23 ± 12.55 and from 70.29 ± 13.33 to 108.48 ± 19.82, respectively. Factors affecting HRQoL of patients with breast cancer included age, education level, income, marital status, lifestyle, tumor stage, method, and treatment duration. Patient's income showed a consistent effect on HRQoL while the remaining factors reported inconsistent findings across the studies. In conclusion, the HRQoL of breast cancer patients in LMICs in Asia was low and affected by several sociodemographic factors which should be studied more in future research.